Details of AT1,AT2 water fountain (RFA-525_Rev E) - WOHA Designs PTE LTD; BUCG-ABC Joint Venture; Web Structures (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of only PDF version of drawings.